A matter of size? Health‐related quality of life after radical prostatectomy for patients with giant prostates. Issue 8 (20th April 2021) - Westhofen, Thilo; Buchner, Alexander; Schlenker, Boris; Becker, Armin; Chaloupka, Michael; Bischoff, Robert; Stief, Christian G.; Kretschmer, Alexander
Abstract: Background: Evidence regarding the impact of giant prostate volume (PV) on outcome after radical prostatectomy (RP) is controversial with a lack of evidence on the impact of PV on health‐related quality of life (HRQOL). We aimed to assess the impact of giant PV on HRQOL and functional outcomes for men with prostate cancer (PC) undergoing RP. Methods: Giant PV was defined based on the 95th percentile of PV measured by specimen weight of 3929 patients that underwent RP between 2013 and 2018 in a large tertiary care center. A propensity score‐matched analysis of 929 men treated with RP for PC ( n = 184 with PV ≥ 100 cm 3, n = 745 with PV < 100 cm 3 ) was conducted. Primary endpoint was the impact of giant PV on HRQOL (based on EORTC QLQ‐C30) assessed with binary logistic regression and Cox proportional hazard model. Secondary endpoint was the impact of PV on oncological‐ and functional outcome. Results: Median follow‐up was 24 months. Median PV, measured by specimen‐weight, was 58 cm 3 . We found no significant differences in median general HRQOL ( p = .183), giant PV was not associated with better HRQOL (odds ratio [OR], 1.54; 95% confidence interval [CI], 0.96–2.47; p = .075). No significant differences were found regarding continence recovery (hazard ratio [HR], 0.956; 95% CI, 0.771–1.185; p = .682), median International Consultation of Incontinence Questionnaire–Short‐Form (ICIQ‐SF) scores ( p = .062) or potency rates ( p = .151). Giant PV did not significantly impair biochemical recurrence‐free survival (HR, 0.968; 95% CI, 0.651–1.439; p = .871). Conclusions: For patients undergoing RP, giant PV was not associated with adverse HRQOL outcomes. We found no significant impact of PV on continence rates, potency rates, and biochemical recurrence‐free survival. Hence, RP is an efficient cancer treatment for men even with giant PV.